In-Plane Seismic Response Analyses of a Historical Brick Masonry Building Using Equivalent Frame and 3D FEM Modeling Approaches. Issue 2 (7th February 2020) - Demirlioglu, Kultigin; Gonen, Semih; Soyoz, Serdar; Limongelli, Maria Pina
ABSTRACT: This article aims at contributing to the seismic performance assessment of a historic brick masonry building by finding a strength reduction coefficient through the use of linear and nonlinear modeling approaches, using Finite Element Method and Equivalent Frame modeling. To reduce the uncertainties, ambient vibration tests (AVT) were implemented. Series of simulations was performed using nonlinear dynamic analyses and incremental dynamic analysis curves were compared with the pushover curves. Results indicate that the mass-proportional pushover curve meets the mean of results obtained from IDA and the strength reduction coefficient falls into the range given in EN 1998–1 for unreinforced masonry.